Improved stability of salvianolic acid B from Radix Salviae miltiorrhizae in deep eutectic solvents. Issue 11 (2nd March 2016) - Chen, Jue; Li, Shi-fei; Yao, Zhi-feng; Yang, Da-wei; Zhang, Li-wei
Abstract : Environmentally friendly deep eutectic solvents were developed for enhancing the stability of salvianolic acid B from Radix Salviae miltiorrhizae . Abstract : Deep eutectic solvents (DESs) have numerous chemical applications as environmentally green solvents due to their unique physicochemical properties. In this study, the stability of salvianolic acid B (SAB) from Radix Salviae miltiorrhizae was investigated in four kinds of benign choline-based DESs modified with different hydrogen-bond donors (ethylene glycol, 1, 2-propanediol, glycerol and 1, 4-butanediol), and the degradation products of SAB were analyzed by high performance liquid chromatography coupled with electrospray ionization tandem mass spectrometry (LC-MS/MS). Obviously, the stability test demonstrated that SAB was more stable in DESs than in water or ethanol solution at room temperature or high temperatures. And the optimum experiment proved that the stabilizing capacity of DESs suffered major influence from the water content in DES solution, minor influence from the structure of hydrogen-bond donors and minimal influence from the molar ratio of quaternary ammonium salts to hydrogen-bond donors. Finally, choline chloride–glycerol (molar ratio 1 : 2) was optimized to offer a satisfactory enhancement effect for the stability of SAB. Moreover, the mechanism of improving stability of SAB in DESs was also discussed by analyzing the content variation trends of degradation products. And the interaction between SAB and DES molecules was also demonstrated by the FT-IR spectrum. Therefore, DESs with stabilizing capacity have great prospects for their applications in the extraction of SAB, even may be further developed as carriers for cosmetic and liquid oral medicines.